The ligamentous cervical instability etiology of human disease from the forward head-facedown lifestyle: emphasis on obstruction of fluid flow into and out of the brain - Hauser, R. A.; Matias, D.; Rawlings, B. (Frontiers in Neurology, 2024)
Ligamentous cervical instability, especially ligamentous upper cervical instability, can be the missing structural cause and/or co-morbidity for many chronic disabling brain and systemic body symptoms and diagnoses. Due to the forward head-facedown lifestyle from excessive computer and cell phone usage, the posterior ligament complex of the cervical spine undergoes a slow stretch termed “creep” which can, over time, lead to cervical instability and a breakdown of the cervical curve. As this degenerative process continues, the cervical curve straightens and ultimately becomes kyphotic, a process called cervical dysstructure; simultaneously, the atlas (C1) moves forward, both of which can lead to encroachment of the structures in the carotid sheath, especially the internal jugular veins and vagus nerves. This obstruction of fluid flow can account for many brain diseases, and compression and stretch of the vagus nerve for body diseases, including dysautonomia. This article describes the consequences of impaired fluid flow into and out of the brain, especially venous flow through the internal jugular veins, leading to intracranial hypertension (formerly called pseudotumor cerebri). Cervical structural, internal jugular vein, and optic nerve sheath measurements are presented from a retrospective chart review of 227 consecutive patients with no obvious cause for 1 of 8 specific brain or mental health symptoms—anxiety, brain fog, concentration difficulty, depression/hopelessness, headaches, obsessive thoughts, panic attacks, and rumination on traumatic events. A case example is given to demonstrate how cervical structural treatments can open up internal jugular veins and improve a patient’s chronic symptoms.